ZEB1 inhibition sensitizes cells to the ATR inhibitor VE-821 by abrogating epithelial–mesenchymal transition and enhancing DNA damage. Issue 5 (4th March 2018) - Song, Na; Jing, Wei; Li, Ce; Bai, Ming; Cheng, Yu; Li, Heming; Hou, Kezuo; Li, Yanrong; Wang, Kai; Li, Zhi; Liu, Yunpeng; Qu, Xiujuan; et al.
ABSTRACT: The ataxia-telangiectasia-mutated (ATM) and rad3-related (ATR) checkpoint pathway plays an essential role in modulating cellular responses to replication stress and DNA damage to maintain genomic stability. In various tumors, cancer cells have increased dependence on ATR signaling for survival, making ATR a promising target for cancer therapy. ATR inhibitors sensitize multiple tumor cell types to radiation and DNA-damaging agents, but application of an ATR inhibitor alone shows limited efficacy. In the present study, we investigated the role of epithelial-to-mesenchymal transition (EMT) and the EMT transcription factor ZEB1 in regulating cell sensitivity to the ATR inhibitor VE-821. We found that VE-821 induced EMT with concomitant ZEB1 upregulation and promoted migration in cells in which the anti-proliferative effect of VE-821 was limited. Knocking down ZEB1 using siRNA partially reversed VE-821-induced EMT, and sensitized cells to VE-821 via effective attenuation of migration and AKT/ERK signaling. Moreover, ZEB1 inhibition promoted Chk1 phosphorylation and induced S-phase arrest by enhancing TopBP1 expression, which suggests a distinctive modulatory effect of ZEB1 on Chk1. Finally, combining VE-821 with ZEB1 inhibition enhanced DNA damage accumulation. These results demonstrate that EMT represents a novel mechanism for limiting the effectiveness of an ATR inhibitor, and thus suggest that ZEB1 inhibition might represent a new approach to increasing the efficiency of, or reversing resistance to, ATR inhibitors.